Sensitivity Analysis of the Bar Structures Reliability - Sieniawska, R.; Śniady, P.; Żukowski, S. (Engineering Transactions, 2000)
In the paper certain theoretical basis and practical approach for design sensitivity analysis of bar structure's reliability under a special type of excitation are presented. The analysis is carried out for the plane bar structures made of linearly elastic material. It is assumed that the structure's physical and geometrical parameters are deterministic variables and a non-Gaussian stochastic process describes the load. Examples for a beam loaded by a stream of moving random forces are presented.